2017
DOI: 10.1155/2017/4148651
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fucosyltransferase 2 Gene Polymorphisms with Inflammatory Bowel Disease in Patients from Southeast China

Abstract: Aims. Fucosyltransferase 2 (FUT2) gene potentially affects the constituent of intestinal microbiota, which play a crucial role in the pathogenesis of inflammatory bowel disease (IBD). This study investigated the association of FUT2 gene polymorphisms with IBD in southeast China. Methods. We collected 671 IBD patients and 502 healthy controls. FUT2 gene polymorphisms (C357T, A385T, and G428A) were determined by SNaPshot. Frequencies of the FUT2 genotypes, alleles, and haplotype between groups were compared by χ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The minor allele (A) confers a nonsecretor phenotype and is associated with Crohn's disease (CD) susceptibility with odds ratio of 1.11 (1.071-1.143 95% CI, p < 10 ¡15 ). [13][14][15] Host-microbe interactions can involve FUT2 through modification of components of the mucus layer, [16][17][18][19] and thus FUT2 is an ideal candidate to test for association with the gut microbiota variability. Indeed several studies have already investigated the role of FUT2 in the composition of the microbiota but large biological (mucosal versus stool sample or bile duct) and technical differences (DNA extraction and profiling method of the microbiota) exist between studies resulting in potentially different results.…”
Section: Introductionmentioning
confidence: 99%
“…The minor allele (A) confers a nonsecretor phenotype and is associated with Crohn's disease (CD) susceptibility with odds ratio of 1.11 (1.071-1.143 95% CI, p < 10 ¡15 ). [13][14][15] Host-microbe interactions can involve FUT2 through modification of components of the mucus layer, [16][17][18][19] and thus FUT2 is an ideal candidate to test for association with the gut microbiota variability. Indeed several studies have already investigated the role of FUT2 in the composition of the microbiota but large biological (mucosal versus stool sample or bile duct) and technical differences (DNA extraction and profiling method of the microbiota) exist between studies resulting in potentially different results.…”
Section: Introductionmentioning
confidence: 99%
“…Fucosyltransferase 2 (FUT2) is one of the detected gene variants in IBD patients, and it is associated with predisposition to IBD in patients of various races. [10][11][12][13] Aheman et al reported that FUT2 gene variants are associated with UC in Han and Uyghur patients in western China. 12 Parmar et al discovered a significant FUT2 mutation in Finish patients with UC and CD.…”
mentioning
confidence: 99%
“…Specifically, CCL11 , an eosinophil-specific chemokine, is significantly elevated in serum of Crohn’s disease patients versus normal controls 27 and has been shown to be a central mediator for eosinophil recruitment in colon 28 . The genetic polymorphisms of Fucosyltransferase 2 ( FUT2 ) have also been associated with Crohn’s diseases in multiple independent genome-wide association studies from distinctive populations 29 , 30 . The role of Autophagy Related 16 Like 1 ( ATG16L1 ) in Crohn’s diseases is even more well-characterized by a large body of literature (See 26 for a comprehensive review).…”
Section: Resultsmentioning
confidence: 99%